Developing a sustainable community forest management strategy in the mountainous areas of Tanggamus, Lampung, Indonesia - MORIZON MORIZON; DODIK RIDHO NURROCHMAT; AWANG MAHARIJAYA; PRABU KRESNA PUTRA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Morizon, Nurrochmat DR, Maharijaya A, Putra PK. 2023. Developing a sustainable community forest management strategy in the mountainous areas of Tanggamus, Lampung, Indonesia. Biodiversitas 24: 4503-4513. The Community Forest (HKm) program allows local communities to legally manage forests to strengthen their rights and reduce conflicts over forest resources. However, the program has yet to be successful in achieving its goals. This study aims to provide recommendations for HKM management strategies. The research involved surveys, field observations, and literature studies. Respondents were selected using purposive sampling and data analysis applied qualitative methods, including triangulation and SWOT analysis. The study found that the social and institutional aspects of the HKM program were not functioning well, with poor relationships among members of the farmers' group (Gapoktan). From an ecological perspective, there has been a decline in plant species. At the same time, the economic aspect shows that only 15% of members benefited from HKM, leaving the rest feeling its negative impact. The study recommends institutional restructuring, coaching, and capacity building for human resources, implementing agroforestry and organic schemes for coffee cultivation, providing guidance on alternative crops such as cardamom, and optimizing the role of cooperatives within the group. Key players must actively participate in HKM management. These recommendations could lead to the effective implementation of the HKM program.